Optical fiber Fabry-Pérot micro-displacement sensor for MEMS in-plane motion stage - Kim, Yong Sik; Dagalakis, Nicholas G.; Choi, Young Man (Microelectronic Engineering, 2018)
Fabry-Pérot interferometer sensors have been widely used in Micro-Electro-Mechanical-Systems (MEMS) due to high displacement accuracy and immunity to electromagnetic noises, but they are still limited by micro scale measurement range. In this paper, a Fabry-Pérot interferometer in-plane displacement sensor is proposed for measuring the displacement of MEMS devices utilizing a polished optical fiber and a modulated laser source. The polished optical fiber and a sidewall of a MEMS device form an optical cavity for the proposed sensor. The sinusoidal phase modulation with extreme point search algorithm enables the proposed sensor to measure displacements larger than the wavelengths of the laser light in real time. The experimental results show that the proposed displacement sensor has a capability to measure displacements larger than 3 μm and it shows the measurement accuracy less than 35 nm. The proposed displacement sensor is then embedded on a single degree-of-freedom MEMS motion stage and tested to monitor its displacement in real time.
Keywords: Displacement sensor; Electromagnetic noise; In-plane displacement; Interferometer sensors; Micro electromechanical system (MEMS); Phase lock; Single degree of freedoms; Sinusoidal phase modulation; Displacement sensor; Distributed feedback laser; Fabry-Pérot interferometry; MEMS; Optical fiber; Phase lock; Sinusoidal phase modulation